"Traditional Food Of Solo Strait As Immaterial Cultural Heritage: Protection, Preservation, And Promotion" - Adityo Putrowidi Bramantyo; Aletta Dewi Maria ; Wahyu Mafatikhul Aulia (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This study aims to examine the role of traditional Solo Straits food as an immaterial cultural heritage and investigate steps that can be taken to protect, preserve, and promote it. The research method used involved literature review, direct observation, interviews with cultural experts, and qualitative data analysis. The results that the traditional food of the Solo Strait has high cultural value as a symbol of tradition, togetherness, local wisdom, hospitality, and cultural identity. However, this traditional food faces threats in the form of changes in lifestyle, the influence of globalization, and the loss of traditional knowledge in food processing and serving. To protect, preserve, and promote the traditional food of the Solo Strait, steps are needed that involve legal recognition and protection, cultural education, preservation activities such as documentation and training, as well as support from the local community and related stakeholders. In addition, promotion strategies through social media, participation in culinary events, collaboration with tourism actors, and development of related products and services are also needed to introduce this traditional food as a culinary tourism attraction and support local economic development. This research provides a deeper understanding of the importance of traditional Solo Straits food as an immaterial cultural heritage and provides recommendations to local governments and local communities to protect, preserve, and promote this traditional food. It is hoped that by adopting the right policies and implementing strategies, the traditional food of the Solo Straits can be protected, preserved, and become a driver of sustainable local economic development.